Robotic single‐access splenectomy using the Da Vinci Single‐Site® platform: a case report. Issue 1 (4th October 2013) - Corcione, Francesco; Bracale, Umberto; Pirozzi, Felice; Cuccurullo, Diego; Angelini, Pier Luigi
Abstract Background Single‐access laparoscopic splenectomy can offer patients some advantages. It has many difficulties, such as instrument clashing, lack of triangulation, odd angles and lack of space. The Da Vinci Single‐Site® robotic surgery platform could decrease these difficulties. We present a case of single‐access robotic splenectomy using this device. Methods A 37 year‐old female with idiopathic thrombocytopenic purpura was operated on with a single‐site approach, using the Da Vinci Single‐Site robotic surgery device. Results The procedure was successfully completed in 140 min. No intraoperative and postoperative complications occurred. The patient was discharged from hospital on day 3. Conclusions Single‐access robotic splenectomy seems to be feasible and safe using the new robotic single‐access platform, which seems to overcome certain limits of previous robotic or conventional single‐access laparoscopy. We think that additional studies should also be performed to explore the real cost‐effectiveness of the platform. Copyright © 2013 John Wiley & Sons, Ltd.